2004
DOI: 10.1152/jn.00818.2003
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Saccadic Responses in Monkey When Multiple Competing Visual Stimuli Are Present

Abstract: Important insights into the neural organization of the saccadic system have been gained when the usually stereotyped movement trajectories of saccades have been altered by experimental manipulation. In the present study we produced trajectory variability in monkeys by using a visual search task in which both the location and color of an odd-colored target were changed randomly trial by trial, and the number of distractors was varied on each trial. We wished to determine whether increasing the number of distrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 40 publications
4
49
0
Order By: Relevance
“…The different response modes in our experiments are quite reminiscent of previous reports from visuomotor experiments, in which two visual targets evoked saccadic eye movements (Becker and Jürgens, 1979;Findlay, 1982;Ottes et al, 1984Ottes et al, , 1985Chou et al, 1999;Aitsebaomo and Bedell, 2000;Watanabe, 2001;Arai et al, 2004;Nelson and Hughes, 2007). Those studies revealed that the visuomotor system typically responds with averaging saccades when stimuli are presented in spatial-temporal proximity, and when the response reaction time is fast.…”
Section: Comparison With Other Studiessupporting
confidence: 80%
See 3 more Smart Citations
“…The different response modes in our experiments are quite reminiscent of previous reports from visuomotor experiments, in which two visual targets evoked saccadic eye movements (Becker and Jürgens, 1979;Findlay, 1982;Ottes et al, 1984Ottes et al, , 1985Chou et al, 1999;Aitsebaomo and Bedell, 2000;Watanabe, 2001;Arai et al, 2004;Nelson and Hughes, 2007). Those studies revealed that the visuomotor system typically responds with averaging saccades when stimuli are presented in spatial-temporal proximity, and when the response reaction time is fast.…”
Section: Comparison With Other Studiessupporting
confidence: 80%
“…Second, in visuomotor experiments, visual stimuli were well separable, both at the retina, and in early sensory responses of neurons within the visuomotor pathways. This holds also for example for the midbrain superior colliculus (SC), a crucial sensorimotor interface for the programming and generation of eyehead orienting responses (Arai et al, 2004;Kim and Basso, 2008). The actual visual response selection leading to either averaging or bimodal responses is therefore attributable to neural processing, rather than to visual peripheral limitations.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The location of the visual target presented in relation to the evoked stimulation vector was loosely chosen to achieve distributions of distances in SC coordinates similar to those collected in experiment 1. Stimulation-evoked saccades that interacted with the visual target showed no obvious signs of curvature (saccades directed first toward one target and then toward the other in midflight; Arai et al 2004;Port and Wurtz 2003) and reflected a weighted combination of the visual and stimulation-evoked saccades; only this subset of movements was analyzed for the purpose of this study. Saccades observed on other trials clearly resembled pure stimulation movements (stimulation onset occurred well before the visually guided saccade), curved saccades (stimulation onset occurred during the visually guided saccade), or pure visual movements (stimulation onset occurred after the visually guided saccade) (McPeek et al 2003;Noto and Gnadt 2009) and were excluded from additional analyses.…”
Section: Experimental Procedures and Behavioral Tasksmentioning
confidence: 99%